Plummer-Vinson Syndrome in Children. Issue 5 (November 2015) - Butori, Mathilde; Mahmoudi, Sana; Dugelay-Ecochard, Emmanuelle; Belarbi, Nadia; Bellaïche, Marc; Hugot, Jean-Pierre; Viala, Jérôme
ABSTRACT: Objectives: Plummer-Vinson syndrome (PVS), also called Kelly-Paterson syndrome, is a rare cause of dysphagia in children. This syndrome associates single or multiple webs in the upper esophagus with frequent iron deficiency. Methods: We reported 3 pediatric cases of PVS before analyzing all of the cases of PVS in children reported in the PubMed and EMBASE databases. Results: Among 17 reported PVS cases in children, all of the patients experienced iron-deficiency anemia, and no immunological disease was reported. The male/female ratio was 1/1.9, and most cases were observed in adolescents. Conversely to adults, endoscopic dilation was often necessary because dysphagia resisted iron supplementation. A single dilation was usually sufficient. One case of pediatric PVS experienced esophageal cancer in adulthood. Conclusions: In the case of dysphagia in children, a swallow barium exploration with lateral incidence should look for PVS. Conversely to adults, an endoscopic dilation is frequently necessary to control dysphagia in children.